An interaction integral retardation model for predicting fatigue life under multi-step loading. (September 2020) - Gadallah, Ramy; Tsutsumi, Seiichiro
Highlights: An interaction integral retardation model is developed to predict fatigue life. The cyclic interaction integral (Δ I ) is based on elasto-plastic concepts. The adequacy of the developed model is verified using different loading conditions. The mechanics of crack growth retardation and acceleration is discussed. The local material behavior is discussed rigorously under variable cyclic loadings. Abstract: This paper proposes an interaction integral retardation (IIR) model to predict fatigue life accurately for components subjected to multi-step loading (MSL) conditions. The IIR model is based on the cyclic interaction integral that considers the effect of elasticity and plasticity simultaneously at the crack tip. Elasto-plastic numerical simulations were carried out based on FEM to compute the cyclic interaction integral. The IIR model was verified against the experiments under different loading conditions including constant amplitude loadings, single tensile overloads, and MSL for different steel strengths. The fatigue lives calculated by the IIR model exhibit a very good agreement with those obtained by the experiments for the applied loading conditions and steels. The efficiency of the IIR model was manifested by comparing the calculated fatigue lives against those computed by different traditional and well-established fatigue crack growth (FCG) models. For the MSL condition, fatigue lives obtained by the IIR model revealed a better agreement against the experiment compared to those given by the traditional FCG models. The crack-tip driving force represented by the elasto-plastic cyclic interaction integral could explain the mechanics of crack growth retardation and acceleration due to the change in the applied loading. Further, the local material behavior ahead of the crack tip was examined rigorously for different crack lengths under variable cyclic loadings. It was found that the local material behavior has a significant influence on the state of crack growth (retardation/acceleration) which results in accelerating or retarding the crack growth rate.